2012
DOI: 10.1186/1749-8090-7-99
|View full text |Cite
|
Sign up to set email alerts
|

The adequacy of single-incisional thoracoscopic surgery as a first-line endoscopic approach for the management of recurrent primary spontaneous pneumothorax: a retrospective study

Abstract: BackgroundThoracoscopic surgery is a commonly used endoscopic surgical treatment approach in patients with primary spontaneous pneumothorax. The conventional thoracoscopic approach utilizes three or more small wounds for surgery. Currently, a single port approach is a potential alternative procedure in general thoracoscopic surgery. We investigated whether a single-port approach is suitable as a first-line endoscopic approach for all patients with primary spontaneous pneumothorax requiring surgery.MethodsFrom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 7 publications
1
14
0
Order By: Relevance
“…The single port access enables the use of a grasping endoscopic instrument, the thoracoscope and an articulated stapler. Surgical instruments entered from different angles could create a three-dimensional working environment (8).…”
Section: Discussionmentioning
confidence: 99%
“…The single port access enables the use of a grasping endoscopic instrument, the thoracoscope and an articulated stapler. Surgical instruments entered from different angles could create a three-dimensional working environment (8).…”
Section: Discussionmentioning
confidence: 99%
“…Uniportal VATS (UVATS) is a singleincision thoracoscopic approach. Some evidence suggests that UVATS may improve postoperative pain, paresthesia, and patient satisfaction as compared with traditional VATS [3][4][5][6]. The role of UVATS in performing lobectomy is not well investigated.…”
mentioning
confidence: 93%
“…Since then, some authors have reported SITS for PSP, and the adequacy of the technique has been discussed. [3][4][5][6][7][8][9] We have also established an original SITS procedure with a single incision 2.0 cm in length and have been using it in PSP patients since 2009. We herein describe the clinical characteristics and surgical results for the first 100 patients who underwent SITS for PSP.…”
Section: Introductionmentioning
confidence: 99%